Import and Export Prices in the United States and the Terms of International Trade, 1880-1914 - Kreps, T. J. (Quarterly Journal of Economics, 1926)
Journal Article Import and Export Prices in the United States and the Terms of International Trade, 1880–1914 Get access T. J. Kreps T. J. Kreps Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 40, Issue 4, August 1926, Pages 708–720, https://doi.org/10.2307/1884462 Published: 01 August 1926